Employment equity in tertiary education: The pitfalls of fast-tracking academics - Geldenhuys, J. (South African Journal of Higher Education, 2020)
During 2018, the South African Human Rights Commission (SAHRC) was requested to hold investigation hearings at the University of South Africa (Unisa). The purpose was, among other things, to provide solutions to problems relating to the lack of meaningful transformation in employment in the institution. Before the finalisation of the investigation hearings, Unisa management began the process of amending the institution’s Employment Equity plan. This contribution, against the setting of the recommendations made for Unisa, considers the different measures that could be implemented to speed up the transformation of the academic workforce in South African universities. After scrutinising the relevant pedagogic, legal and social implications of the implementation of different affirmative action measures, several potential pitfalls or potentially negative consequences of affirmative action measures not promoting the academic project are identified. It is concluded that developing an individual into a mature academic should not be forced or fast-tracked because of the possible negative consequences for both individuals and the academic project as a whole. Moreover, making academic appointments and promotions without considering crucial factors such as experience, publications and knowledge is bound to have a devastatingly negative impact. Enhancing the skills of employees in the designated groups would appear to be the best way of levelling the academic playing field.